Effect of lithium additive on the microstructure and electrical responses of 0.9PMN-0.1PT ceramics - Cavalheiro, Alberto Adriano; Bruno, Juliana C.; Zaghete, Maria A.; Varela, José Arana [UNESP] (Springer, 2007)
Structural effects of lithium additive on 0.9PMN-0.1PT powders prepared by Ti-modified columbite route were studied. The substitution of Li+ ions for Mg2+ ions in the B-site sub-lattice of 0.9PMN-0.1PT perovskite structure was explained in terms of lead and oxygen vacancies generation originated as consequence of the ionic compensation of negatively charged Li'(Mg) sites. The rise in mass transport as consequence of the increasing of Pb2+ and O2- vacancies produces more agglomerated particles during the powder synthesis and changes the mechanical characteristics between grain and grain boundary of sintered ceramic. The relation between K-m and T-m values, the difference between ionic radii of B cation and the molar volume were used to explain the changes in the relaxor behavior and diffusiveness of phase transition as function of lithium doping, which are corroborated by the results obtained through the ferroelectric characterization.